Strategi Pengembangan Produk Pembiayaan Dalam Upaya Peningkatan Kapasitas UMKM Pada BPRS UMMU di Bangil Pasuruan - Nila Safira Ramadhanty; Renny Oktafia (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2021)
This study aims to determine the strategy of developing financing products in an effort to increase the capacity of micro, small and medium enterprises (MSMEs) at Islamic people’s financing bank (BPRS) UMMU in Bangil Pasuruan. This type of research uses qualitative methods. Data sources used in this study are primary data and secondary data. Data collection techniques used were interviews and documentation. The results of this study ate the existence of BPRS UMMU in Bangil Pasuruan is very beneficial for the community especially thosr who have small an medium micro businesses because with the financing can help in terms of capital, increase the capacity to trade and help sustain the economy in Bangil Pasuruan.